QUALITY CONTROL OF HYDRAULIC LIQUID OF «HYDRONIKOIL» FH-51 AT THE PROTRACTED USE: PROBLEMS AND TASKS - Кузнєцова, О. Я. (Science-based technologies, 2014)
In the directive of ІCАО Doc 9735 tasks are set forth on creation in every state of corresponding national organs for control of activity on providing of safety of flights and connections on these questions with the committees of ICАО. The operating national checking of quality control system of hydraulic liquids is regulated by Instruction that is ratified in 2006 and worked out with the use of out-of-date normatively-legal acts. Until now additions, that would reflect the tasks set forth in Doc 9735 in the direction of quality control of hydraulic liquids at protracted, are not brought in Instruction. It is experimentally set that at the protracted use of hydraulic liquid of «Hydronikoil» FH-51 compounds that cause to reduction of her oxidizing stability appear. The existent quality control system is not able to forecast the change of operating properties of hydraulic liquid at the protracted use. Therefore is not possible to foresee development of refuses and disrepairs of aggregates of the hydraulic system of air ship, that creates the serious threat of safety of flights. Taking into account aforesaid, it is necessary to harmonize the operating quality control system of hydraulic liquids in accordance with the tasks of ICАО; to work out control system quality of hydraulic liquids at the protracted use; to create the system of providing of safety of flights in the part regarding to the protracted use of hydraulic liquids; to harmonize these systems with modern international requirements, taking into account national features.